IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK KELAS IV DI SDN GUNUNG PICUNG 07 PAMIJAHAN BOGOR - Apriliani, Astri; Hasanah, Tita; Ihsan, Muzhir (Prodi PGMI IAI Sahid, 2025)
This research discusses the implementation of the Pancasila Student Profile Strengthening Project (P5) in forming the character of class IV students at SDN Gunung Picung 07 Pamijahan Bogor. The aim of this research is to analyze the implementation of the Pancasila Student Profile Strengthening Project in forming the character of students and to analyze the obstacles faced by teachers in implementing the Pancasila Student Profile Strengthening Project. The research method uses qualitative field research. The research object consisted of key informants, namely the school principal and grade IV teacher specialization informants. Data collection techniques in this research used interviews, observation and documentation. Data analysis was carried out using the Triangulation technique. The research results conclude two main points. First, the implementation of P5 at SDN Gunung Picung 07 in forming the character of students, namely by applying the six dimensions of the Pancasila Student Profile, namely: 1) Having faith, being devoted to God Almighty and having noble character; 2) Independent; 3) Working together; 4) Global diversity; 5) Critical reasoning; and 6) Creative. Second, the obstacles faced by teachers in implementing P5 at SDN Gunung Picung 07, namely: 1) lack of understanding and support for the implementation of P5 in the independent curriculum; 2) difficulty in creating the P5 Project Module; and 3) the difficulty of instilling the values ​​of the Pancasila Student Profile Strengthening Project in students.